Penguatan Kewirausahaan berbasis SMART Marketing di Sekolah Menengah Kejuruan - Yasser Abd. Jawad; Faisal Syafar; Darlan Sidik; Lu'mu; Halimah Husain (Sakura Digital Nusantara, 2023)
The community collaboration initiative developed at SMK Negeri 7 Makassar will offer instructional sessions. This exercise comprises a total of 20 participants, with 13 being students and 7 being teachers. Every participant will receive training and guidance on how to deliver Smart Marketing-based Entrepreneurship Strengthening, which encompasses defined, quantifiable, realistic, relevant, and time-bound objectives. Moreover, equipped with expertise in management and entrepreneurship, PKM participants can enhance their self-reliance in generating employment opportunities aligned with their skill sets. The activity employs project-based learning as its methodology. Offers information regarding the significance of increasing entrepreneurship. Presents concise strategies for launching a self-sustaining enterprise and cultivating an enterprising mindset through the implementation of intelligent marketing techniques. The lecture and question and answer style is employed to elucidate the subject matter and present case examples that serve as sources of inspiration for the participants. The Entrepreneurship Program, which is centered around digital technology, provides a comprehensive understanding of the various types and roles of the digital revolution in the field of Marketing.